Analyzing Grammatical and Lexical Cohesion in A Legendary Short Story - Noprival Noprival; Alfian Alfian; Robi Soma (Indonesian Journal of EFL and Linguistics, 2022)
Analyzing Grammatical and Lexical Cohesion in A Legendary Short Story Noprival Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, Jambi, Indonesiae-mail: noprival@gmail.com (corresponding author) Alfian Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Jambi, Indonesiae-mail: alfian@uinjambi.ac.id Robi SomaUniversitas Jambi, Jambi, Indonesiae-mail: robisoma858@unja.ac.id Abstract:Despite the existence of many studies on cohesion in discourse, little scholarly work reports grammatical and lexical cohesion in a short story. To fill this gap, the present study investigates these two aspects of cohesion in a legendary short story entitled “After Twenty Years.” Halliday and Hasan’s (1976) theoretical framework of cohesion was used to guide the current study. We applied textual analysis as the appropriate approach to find out grammatical and lexical cohesion within the forms of text. The findings in the grammatical cohesions showed that reference had the highest frequency of the total cohesive devices. Also, under grammatical cohesion, conjunctions are found to exist. However, other aspects were not found within this short story, including substitution and ellipsis. On the other hand, repetition was dominantly used lexically among other aspects of lexical cohesion and sequentially followed by repetitions, hyponyms, synonyms, and antonyms. Only one aspect of lexical cohesion, the meronym, was not found.  The overall results of the research indicated that the short story was a coherent discourse because both grammatical and lexical cohesion exist properly.